1990
DOI: 10.1002/cber.19901231205
|View full text |Cite
|
Sign up to set email alerts
|

Neuartige basische Liganden für die homogenkatalytische Methanolcarbonylierung, XXXVIII. Synthese, Eigenschaften und fluktuierendes Verhalten von (Ether‐Phosphan)palladium‐Komplexen

Abstract: Novel Basic Ligands for the Homogeneous Catalytic Carbonylation of Methanol, XXVIII''. -Synthesis, Properties and Fluxional Behavior of (Ether-Ph0sphine)palladium Complexes Cl,Pd(COD) (1) (COD = 1,5-cyclooctadiene) reacts with 1 equiv. of the (ether-phosphine) ligand PhzP-D (2a-c) [D = CH;!C4H70 (a), CH2C4H702 (b), CH2CH20CH3 (c)] to give the dimeric complexes [p-ClPdCl(Ph,P-D)], (3a-c) (P-D = ql-P-coordinated). According to the field-desorption mass spectra which show only one peak for the monomeric moieties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We are aware of only a single recent report on such a process in imidazolylphosphine complexes, however, without data on the activation parameters . There are a few examples in pyrid-2-ylphosphine chemistry of complexes with one chelating and one nonchelating phosphine, some without exchange and others with some evidence of exchange. There are examples of other hemilabile Pd complexes, for example ones with pyridylphosphines in which the heterocycle and the phosphine are separated by several atoms, or complexes with phosphines containing ethers as well as other functional groups , the differences in ligand type or metal preclude any meaningful comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of only a single recent report on such a process in imidazolylphosphine complexes, however, without data on the activation parameters . There are a few examples in pyrid-2-ylphosphine chemistry of complexes with one chelating and one nonchelating phosphine, some without exchange and others with some evidence of exchange. There are examples of other hemilabile Pd complexes, for example ones with pyridylphosphines in which the heterocycle and the phosphine are separated by several atoms, or complexes with phosphines containing ethers as well as other functional groups , the differences in ligand type or metal preclude any meaningful comparison.…”
Section: Resultsmentioning
confidence: 99%
“…73 nonchelating phosphine, some without exchange [92][93][94] and others with some evidence of exchange. [95][96][97] There are examples of other hemilabile Pd complexes, for example ones with pyridylphosphines in which the heterocycle and the phosphine are separated by several atoms, [98][99][100] or complexes with phosphines containing ethers 101 as well as other functional groups. 10 However, in most cases activation energies were not reported, or in the cases where this information is available, 99,102 the differences in ligand type or metal preclude any meaningful comparison.…”
Section: Steric Interactions Between Ligands Become Especially Appare...mentioning
confidence: 99%
“…To mention a few, Kantam et al [16] reported good conversions at room temperature in reduction of nitro aromatics to their aromatic amines with Pd-MCM(II) catalysts. Han and Jang [17] reported the reduction of nitro aromatics using montmorillonite clay (K-10) with anhydrous hydrazine (1:6 molar ratio) in ethanol under reflux conditions in nitrogen atmosphere for 2 h. Carlini et al [18] investigated many mono [19][20][21] and diphosphine [22][23][24][25][26] modified complexes, such as diphsophine polymer-bound palladium complexes, which can be prepared in few steps, as catalysts, but gave low conversions. Sudalai et al [27] reported hydrogen transfer reaction of nitro aromatics on Ni-zirconia catalysts at reflux temperature, which required the use of stoichiometric amounts of base to enhance the reaction.…”
Section: Introductionmentioning
confidence: 99%